An educator's guide to assessing threats in student writing : social media, email, and other narrative - Van Brunt, Brian; Lewis, W. Scott; Solomon, Jeffrey H. (New York: Routledge, 2021)
"Based on research from the threat assessment community, this important resource addresses the challenge of assessing concerning online communication, written narratives, and artistic works at schools, colleges, and universities. Drawing from the collective fields of law enforcement, law, and psychology, the authors expand on evidence-based practices to help student affairs staff and K-12 educators best assess the validity of these communications and develop intervention and management plans. Concepts are supported through numerous examples of social media posts, written fiction work, emails and examples from past attacks, as well as averted plans. Appropriate for the classroom, Behavioral Intervention teams, front-line teaching staff, and administrators, this new resource will ensure an evidence-based approach to early assessment and intervention"--
Includes bibliographical references and index.
Keywords: School violence -- Prevention; Threats of violence -- Evaluation; School prose